2014
DOI: 10.1155/2014/134862
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection against Ischemia/Reperfusion by Licochalcone B in Isolated Rat Hearts

Abstract: The generation of reactive oxygen species (ROS) is a major cause of heart injury induced by ischemia-reperfusion. The left ventricular developed pressure (LVDP) and the maximum up/down rate of left ventricular pressure (±dp/dt max⁡) were documented by a physiological recorder. Myocardial infarct size was estimated macroscopically using 2,3,5-triphenyltetrazolium chloride staining. Coronary effluent was analyzed for lactate dehydrogenase (LDH) and creatine kinase (CK) release to assess the degree of cardiac inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 28 publications
3
46
0
1
Order By: Relevance
“…34 In accordance with a previous study, 35 our present study demonstrated that A/R exposure significantly increased ROS production in H9c2 cells, thereby increasing the levels of MDA, which is an oxidative stress marker (Fig. 34 In accordance with a previous study, 35 our present study demonstrated that A/R exposure significantly increased ROS production in H9c2 cells, thereby increasing the levels of MDA, which is an oxidative stress marker (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…34 In accordance with a previous study, 35 our present study demonstrated that A/R exposure significantly increased ROS production in H9c2 cells, thereby increasing the levels of MDA, which is an oxidative stress marker (Fig. 34 In accordance with a previous study, 35 our present study demonstrated that A/R exposure significantly increased ROS production in H9c2 cells, thereby increasing the levels of MDA, which is an oxidative stress marker (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Along these lines, inflammation plays a key role in cardiac I/R injury, and the harmful reactions that follow these reactions include an elevated release of proinflammatory cytokines (such as CRP, TNF-α and IL-6) (Han et al, 2014; Li and Ye, 2015). Studies have demonstrated that several chemically distinct agonists of PPARγ reduce myocardial infarct size caused by regional I/R in rats (Goyal et al, 2011; Hu Q. et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In our study; Losartan pretreatment in animal model of I/Rat a dose of 20 mg/kg/day for 6 weeks before induction of I/R achieved a biochemical cardioprotective effect through reduction of I/R induced elevation of IL-6, TNF-α and CRP. Angiotensin II is described as a potent pro-inflammatory mediator causing up regulation of macrophages to induce inflam- 19 Furthermore, angiotensin II has been found to have a dual effect on macrophages through activation of the mitogenactivated protein kinase (MAPK) pathway and up-regulation of early growth response-1 (Egr-1) gene expression which both master the switch for vascular inflammatory responses.…”
Section: Discussionmentioning
confidence: 54%
“…On the contrary, lowering of CK-MB levels was reported in the effluent liquid of an isolated heart model linked to langend off reperfused apparatus where the heart was pretreated with valsartan before induction of I/R. 26 The discrepancy in losartan effect on CK-MB levels between the two animal models may be ascribed to the difference in study design where our model was in vivo, while the other study 26 was in vitro. In vitro model of I/R allowed direct perfusion of the ang II blocker (valsartan) to the heart while in our study losartan was administered orally, so in vitro model may achieve better availability of the drug to the heart than in vivo model.…”
mentioning
confidence: 86%